Design of algebra digital book on mixed reality-based to improve learner's numeracy literacy - Nugroho, Aryo Andri; Dwijayanti, Ida; Prayito, Muhammad; Noordin, Muhammad Khair; Fenyvesi, Kristof (JRAMathEdu (Journal of Research and Advances in Mathematics Education), 2024)
The development of digital technology in the world of education is currently growing very rapidly, one of which is digital books. Digital books become more interesting if they can present the real environment around students in a virtual form. One technology that can present the real world environment into digital objects and can interact is Mixed Reality. The purpose of this research is to produce a Mixed Reality-based Digital Book on algebra material that is valid and feasible to use in improving students' numeracy literacy skills so that it can support learning. This study uses the Borg and Gall research and development pattern method. Data is taken through expert validation and readability tests for product testing. In the media expert validation which includes general aspects, aspects of learning presentation, aspects of language feasibility, aspects of graphics meet the valid criteria with an average value of five validators 89.2%. In the material expert validation which includes general aspects, aspects of material substance, learning aspects, aspects of usefulness meet the valid criteria with an average score of five validators 92.6%. In the readability test, teachers and lecturers obtained an average of 86% and the readability test on students obtained an average of 80%. Based on the results of media and material validation along with the Mixed Reality-based Digital Book readability test on algebra material, it is concluded that it is valid and feasible to use. The implication of this research is that it makes it easier for students to learn by using digital books to support learning in the classroom so that they can improve their achievement.